Predictive modeling of ICT usage among business education teachers in tertiary colleges of Northwestern Nigeria - Isiyaku, Dansarki Dauda (2015)
The purpose of this study was to propose a structural model to explain and predict teachers’ ICT usage behaviour based on the interrelationships among subjective norm, job relevance, computer self-efficacy, perceptions of facilitating conditions, perceived enjoyment and perceived ease of use, perceived usefulness, attitude towards technology, behavioural intention and ICT usage (as endogenous variables). The theoretical underpinning of the study was established from the Theory of Reasoned Action, Theory of Planned Behaviour and the Technology Acceptance Model (TAM). Almost two decades since the initiation of Nigeria’s information technology policy,the country is still being ranked backward in ICT adoption and use (around Africa and across the world) especially for education. The country’s education sector has been characterized by lack of adequate ICT facilities and lack of skilled ICTmanpower,with most teachers using obsolete tools in the classroom and only a few -buying and using ICTs out of their own volition. Overall, teachers’ use of ICTs in tertiary schools’ classrooms is presently very low in Nigeria and research initiatives on usage of ICTs are rare and predominantly descriptive in nature. This study was a survey research design, conducted in the Northwestern zone of Nigeria, which comprises of seven States, namely: Kano, Jigawa, Katsina, Kaduna,Sokoto, Kebbi and Zamfara. The instrument of data collection was a structured questionnaire, titled ICTUS, adopted from previously validated studies. A pilot study was conducted on a sample of 30 business education teachers whereby an averageCronbach alpha reliability of .75 was obtained on the instrument. During the final study, conducted on a sample of 212 business education teachers, the reliability coefficient ranged from .819 to .956. The study data was analyzed using SPSS 21 for descriptive statistics and AMOS 21 for structural equation modeling. The structural model of the study with 11 paths was tested and found fitting as per the set criteria. Out of the 11 paths in the model five paths have shown significant effects in the interrelationships explained by the model, while six paths have not. The paths that reflected significant effects were as follows: teachers‘ perception of the relevance of ICTs to their jobs influences their perceived usefulness of ICTs ( =.327, p<.001); teachers‘ computer self-efficacy influences their perceived usefulness of ICTs ( = .488, p<.001); teachers‘ perceived enjoyment of ICTs influences their intention to use the ICTs for classroom purpose ( = .724, p<.001); teachers‘ perceived usefulness of ICTs influences their ICT attitude ( = .709, p<.001) and teachers‘ ICT attitude predicts their intention to use ICTs ( = .172,p<.001). On the other hand, the paths with non-significant effects were: teachers‘subjective norm does not predict their intention to use ICTs ( = .016, p>.05);teachers‘ computer self-efficacy does not influence their perception of the ease of use of ICTs for classroom purpose ( = .135, p>.05); teachers‘ perception of facilitating conditions does not influence their perception of the ease of use of ICTs for classroom purpose ( = -.064, p>.05); teachers‘ perceived ease of use of ICTs does not influence their perception of the usefulness of ICTs for classroom purpose ( = - .109, p>.05); teachers perceived ease of use of ICTs does not influence their attitude towards using ICTs for classroom purpose ( = .017, p>.05) and teachers‘ intention to use ICTs does not influence their usage of ICTs for classroom purpose ( = .078,p>.05). In addition to the significant paths in the proposed study model, the modification indices for the proposed model have revealed five new paths with significant effects in the interrelationships among the variables investigated in the study. The new paths were as follows teachers‘ subjective norm influences their attitude towards ICTs, ( =.156, p<. 05); teachers‘ perceived enjoyment of ICTs influences their attitude towards ICTs, ( = .318, p<. 05); teachers‘ computer self-efficacy influences their ICT usage behaviour, ( = .447, p<.001); teachers‘ perception of facilitating conditions influences their ICT usage behaviour, ( = .151, p<.05) and teachers‘ attitude towards technology influences their ICT usage behaviour, ( = .303, p<.001). Overall, the modified structural model of the study with 16 paths has explained about 40% of the variance in the ICT usage behaviour of business education teachers in tertiary colleges of Northwestern Nigeria.